An Econometric Analysis of Deficit Budget, Money Supply and Inflation in Nepal - Bhusal, Tara Prasad (Tribhuvan University Journal, 2013)
High money supply (M2) and high budget deficits (BD) both are equally responsible for higher rate of inflation. Moreover, inflationary pressure gets more momentum when money supply and budget deficits both increase together. The empirical evidence of Nepal also supports this hypothesis. Present paper re-examines this issue in the context of Nepal by using econometric analysis. The empirical results reveal that long run inflation is not only related with higher money supply but also to budget deficit. On the one hand, there is unidirectional causal relationship between money supply with inflation and similarly budget deficit with inflation. On the other, the supply of money has no causal connection with budget deficit. Hence the finding implies that both monetary and fiscal policies are important to control inflation in Nepal.